Pengujian Black Box pada Aplikasi Penjualan Toko Bunga Pelangi Berbasis Web Menggunakan Metode Equivalence Partitioning - Aries Saifudin; Sri Mulyati; Rizki Gustianto Sidi; Riki Firmansyah Tanjung; Isa Hermawan; Nanda Noverdi Ruziki (Jurnal Informatika Universitas Pamulang, 2022)
Application or software testing requires validation to determine whether it meets the desired specifications or not. If the validation process is not perfect, it can result in imperfect data stored or processed, for example, such as when we store data in applications or software whose validation process is not perfect, it can result in errors in the data storage process. So the quality of validation must be improved to be accurate so as not to hinder the use of the software. In this study, we use Blackbox testing with the Equivalence Partitioning method, so that weaknesses in the application or software will be known after testing. The system test results show that the test can improve the quality of the application or the software is free from errors.